Inusual caso de migración de un catéter atrial a las arterias pulmonares - Villamil, Facundo (Revista Argentina de Neurocirugía, 2021)
Cardiac migration of distal ventriculo- atrial catheter is an infrequent and potentially severe complication.In this article, we present a case of a female patient with history of Dandy Walker malformation with requirement of CSF shunting and three replacements that consulted at our institution with abdominal pain, anorexia and nausea secondary to CSF ascites and peritonitis. Therefore, ventriculoatrial shunt was the treatment of choice.Six months later, the patient presented with clinical manifestations of acute hydrocephalus. Brain CT was performed demonstrating distal catheter disconnection from the valve and chest Rx displayed distal cardiac migration of it.Surgical treatment was decided together with a cardiovascular surgeon and the catheter was removed by an endovascular trans femoral approach. After removal of it, a new valve was positioned and a new distal catheter was introduced into the atrium with improvement of symptoms.Treatment of this unusual complication and its interdisciplinary management are discussed.